Epidemiology of Escherichia coli Bacteremia: A Systematic Literature Review. (14th May 2020) - Bonten, Marc; Johnson, James R; van den Biggelaar, Anita H J; Georgalis, Leonidas; Geurtsen, Jeroen; de Palacios, Patricia Ibarra; Gravenstein, Stefan; Verstraeten, Thomas; Hermans, Peter; Poolman, Jan T
Abstract: Background: Escherichia coli is the most common cause of bacteremia in high-income countries. To enable the development and implementation of effective prevention strategies, a better understanding of the current epidemiology of invasive E. coli infections is needed. Methods: A systematic review of literature published between 1 January 2007 and 31 March 2018 on the burden and epidemiology of E. coli bacteremia in populations that include adults in high-income countries was conducted. Meta-analysis was performed for descriptive purposes. Results: During the studied time interval, the estimated incidence rate of E. coli bacteremia was 48 per 100 000 person-years, but this increased considerably with age: rates per 100 000 person-years were >100 in 55-to-75-year-olds and >300 in 75-to-85-year-olds. Overall, E. coli accounted for 27% of documented bacteremia episodes: 18% if hospital acquired, 32% if community-onset healthcare associated, and 33% if community acquired. The estimated case fatality rate was 12%. Approximately 44% of episodes were community acquired, 27% community-onset healthcare associated, and 27% hospital acquired. Urinary tract infection (UTI) was the primary source for 53% of episodes. Conclusions: This systematic review confirms the substantial burden of E. coli bacteremia in older adults and justifies the implementation of community-level programs to prevent E. coli bacteremia and ideally UTI in this age group. Abstract : This systematic review regarding the epidemiology of Escherichia coli bacteremia in high-income countries shows that the disease burden is greatest in the elderly, and that most episodes have a community onset and result from urinary tract infection.